Influence of ergosterol and phytosterols on wine alcoholic fermentation with Saccharomyces cerevisiae strains - Girardi-Piva, Giovana; Casalta, Erick; Legras, Jean-Luc; Nidelet, Thibault; Pradal, Martine; Macna, Faïza; Ferreira, David; Ortiz-Julien, Anne; Tesnière, Catherine; Galeote, Virginie; Mouret, Jean-Roch (Frontiers in Microbiology, 2022)
Sterols are a fraction of the eukaryotic lipidome that is essential for the maintenance of cell membrane integrity and its good functionality. During alcoholic fermentation, they enhance yeast growth, metabolism and viability, as well as resistance to high sugar content and ethanol stress. Grape musts clarified in excess lead to the loss of solid particles rich in sterols, resulting in sluggish and stuck fermentations. Two sterol sources can help Saccharomyces cerevisiae yeasts to adapt to fermentation stress conditions: ergosterol (synthesized by yeast under aerobic conditions) and phytosterols (plant sterols imported by yeast cells from grape musts under anaerobiosis). Little is known about the physiological impact of phytosterols assimilation in comparison to ergosterol and the influence of sterol type on fermentation kinetics parameters. Moreover, studies to date have analyzed a limited number of yeast strains. Thus, the aim of this work was to compare the performances of a wide set of Saccharomyces cerevisiae wine strains fermenting with phytosterols or ergosterol under two conditions: sterol limitation (sterol starvation) and high sugar content (the most common stress during fermentation). Results indicated that yeast cell viability was negatively impacted by both stressful conditions, resulting in sluggish and stuck fermentations. This study revealed the huge phenotype diversity of the S. cerevisiae strains tested, in particular in terms of cell viability. Indeed, strains with better viability maintenance completed fermentation earlier. Interestingly, we showed for the first time that sterol type differently affects a wide variety of phenotype, such as: viability, biomass, fermentation kinetics parameters and biosynthesis of carbon central metabolism (CCM) metabolites. Ergosterol allowed preserving more viable cells at the end of fermentation and, as a consequence, a better completion of fermentation in both conditions tested, even if phytosterols also enabled the completion of alcoholic fermentation for almost all strains. These results highlighted the essential role of sterols during wine alcoholic fermentation to ensure yeast growth and avoid sluggish or stuck fermentations. Finally, this study emphasizes the importance of taking into account sterol types available during wine fermentation.